The influence of bone marrow- and synovium-derived mesenchymal stromal cells from osteoarthritis patients on regulatory T cells in co-culture - Hagmann, Sébastien; Gotterbarm, Tobias; Müller, Thorsten; Bäsig, Anna-Maria; Gantz, Simone; Dreher, Thomas; Frank, Sebastian; Zeifang, Felix; Moradi, Babak (Clinical & experimental immunology, 2013)
There is increasing evidence that inflammation in the synovium plays a major role in the progression of osteoarthritis (OA). However, the immunogenic properties of mesenchymal stromal cells (MSCs), which are considered to regulate immunity in various diseases, remain largely unknown in OA. The purpose of this study was to determine the influence of MSCs from OA patients on regulatory T cells (Tregs) in an allogeneic co-culture model. Bone marrow (BM) and synovial membrane (SM) were harvested from hip joints of OA patients and co-cultured with lymphocytes enriched in CD4+CD25+CD127- regulatory T cells (Treg+LC) from healthy donors. Treg proportions and MSC markers were assessed by flow cytometry. Cytokine levels were assessed after 2 and 5 days of co-cultivation. Additionally, Treg+LC cultures were analysed in the presence of interleukin (IL)-6 and MSC-supernatant complemented medium. B-MSCs and S-MSCs were able to retain the Treg proportion compared to lymphocyte monocultures. T cell-MSC co-cultures showed a significant increase of IL-6 compared to MSC cultures. S-MSCs produced higher amounts of IL-6 compared to B-MSCs, both in single and T cell co-cultures. The effect of retaining the Treg percentage could be reproduced partially by IL-6 addition to the medium, but could only be observed fully when using MSC culture supernatants. Our data demonstrate that retaining the Treg phenotype in MSC-T cell co-cultures can be mediated by MSC derived from OA patients. IL-6 plays an important role in mediating these processes. To our knowledge, this study is the first describing the interaction of MSCs from OA patients and Tregs in an allogeneic co-culture model.
Gesehen am 23.02.2021